Impacto do tipo de inóculo e das condições operacionais sobre a estrutura da comunidade bacteriana e desempenho do processo anammox em biofiltros usando espuma de poliuretano como meio suporte dos microrganismos - Maria Cristina Monteiro de Souza Costa (2014)
The anaerobic ammonium oxidation (Anammox) is catalyzed by anaerobic, chemolithoattotrophic bacteria and is the last discovered microbial pathway in the biological nitrogen cycle, and a new cost-effective method for removal of ammonium from wastewater. This process has been widely studied as alternative in the removal of ammonium nitrogen from wastewater due to its efficiency, lower operating costs and environmental sustainability. This study evaluates the impact of type inoculum and operating conditions on the performance of the Anammox process and microbial structure developed in reactors . Two reactors (RI and RII) of 2L, up flow fixed bed biofilm contínuos were used . Two types of inoculum were applied: one sludge coming from wastewater treatment wetland health-built (CePTS) systems, and the second coming from the treatment of industrial effluent (REGAP / Petrobras) system. These sludges were previously selected for positive PCR results presented for the detection of Anammox bacteria. The diversity of Anammox bacteria inoculum was assessed by cloning technique. The sample of the constructed wetland (inoculated in RI) was dominated by Anammox single genus, "Candidatus" Brocadia while REGAP sludge (inoculated in RII) presented three genera of Anammox : Ca. Anammoxoglobus, Ca Kuenenia and Ca. Brocadia and with predominance of Ca. Anammoxoglobus and Ca. Brocadia . It was possible to develop, Anammox activity and biomass from selected. Results reactors monitoring showed that it was possible to develop Anammox activity and biomass from selected after a year of cultured. The average ammonium and nitrite removal efficiencies of 97% were obtained after one year of operation, based on the influent NH4 +-N and NO2 --N concentrations of 110 and 145mg L-1 for both reactors respectively. The analysis of the microbial diversity of samples collected in the reactors RI and RII, after 440 days of operation, obtained by pyrosequencing technique, demonstrated that the enriched community in the reactors showed different composition, despite similar operating conditions. But the predominant groups were similar. The dominant phyla detected in both reactors were Proteobacteria, Chloroflexi, Planctomycetes and Acidobacteria. However, the phyla Acidobacteria and GN04 were first observed in Anammox reactors, suggesting its importance in this process. Regarding the Anammox community developed after 440 days of operation of the reactors, was concluded that similar operating conditions used in enrichment, selected the same Anammox population , belonging to the genus Ca. Brocadia in both reactors, despite the differences observed in the initial inoculum. Therefore, the selected sludge were able to develop the active Anammox biomass in the reactors after cultivation and operation under anoxic and autotrophic conditions. It was also observed that inocula have impact on the composition of the microbial biomass developed in the reactors, but the operating conditions applied play an important role in the selection of Anammox bacteria community.